Prediction of the saturated hydraulic conductivity from Brooks and Corey's water retention parameters. Issue 5 (28th May 2013) - Nasta, Paolo; Vrugt, Jasper A.; Romano, Nunzio
Key Points Model to predict Ks from the water retention parameters Treatment of connectivity and tortuosity Exploitation of the pore‐size distribution through physically based concepts